2017
DOI: 10.1111/ejss.12494
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and antibiotic resistance from animal manures to soil: a review

Abstract: SummaryThe overuse of veterinary antibiotics in animal production and the subsequent land applications of manures contribute to the elevated antibiotic resistance in the soil environment. To minimize the risk of antibiotic resistance, it is important to understand the fate of antibiotics and the spread of antibiotic resistance genes (ARGs) from animal production systems to soil. In this paper, we review recent studies on veterinary antibiotic use, the concentrations of antibiotics and the abundance and diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(139 citation statements)
references
References 108 publications
(229 reference statements)
1
130
1
7
Order By: Relevance
“…These genes encode three mechanisms that endow bacteria with antibiotic resistance: active antibiotic efflux (tet(A), tet(B), tet(C), tet(D), tet(E), tet(G), tet(H), tet(I), tet(J), tet(Z)), ribosome protection (tet(M), tet(O), tet(S), tet(W), tet(Q), tet(T)), and antibiotic detoxification (tet(X)) (Suzuki et al 2015;Chopra and Roberts 2001). An adaptation and development of antibiotic resistance in soil microorganisms has already been reported for antibiotic-spiked soil samples (Xie et al 2017).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These genes encode three mechanisms that endow bacteria with antibiotic resistance: active antibiotic efflux (tet(A), tet(B), tet(C), tet(D), tet(E), tet(G), tet(H), tet(I), tet(J), tet(Z)), ribosome protection (tet(M), tet(O), tet(S), tet(W), tet(Q), tet(T)), and antibiotic detoxification (tet(X)) (Suzuki et al 2015;Chopra and Roberts 2001). An adaptation and development of antibiotic resistance in soil microorganisms has already been reported for antibiotic-spiked soil samples (Xie et al 2017).…”
Section: Introductionmentioning
confidence: 84%
“…Despite the fact that antibiotics and resistance genes are recognized as a serious environmental problem and many studies (Martinez 2009;Xie et al 2017;Sharma et al 2016) are devoted to assessing their content in water, bottom sediments, and soil and plants, information on the level of their presence in the natural environment in Russia is practically absent.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the long-term application of animal manure and biosolids to agricultural soil may lead to the introduction, proliferation, and dissemination of these emerging contaminants in the environment [181][182][183][184][185]. It was reported that the repeated exposure of the soil environment to amendment-borne ARGs correlates with the emergence and proliferation of ARGs in indigenous soil bacteria [186,187].…”
Section: Emerging Contaminantsmentioning
confidence: 99%
“…Several recent reviews have highlighted these links (e.g. Cakmak & Kutman, ; Li et al, ; Oliver & Gregory, ; Steffan et al, ; Stockamp & Thompson, ; Wall et al, ; Xie et al, ). Nevertheless, many questions still remain.…”
Section: Soil and Human Health – An Essential Area Of Researchmentioning
confidence: 99%